2004
DOI: 10.1017/s1481803500009593
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous magnesium for acute benign headache in the emergency department: a randomized double-blind placebo-controlled trial

Abstract: Background: Magnesium deficiency may play a role in the pathogenesis of migraines and other headaches. Studies in outpatient clinics have found that magnesium administered intravenously (IV) reduces headache pain. We investigated the effectiveness of IV magnesium in patients with acute benign headache who presented to the emergency department (ED). Methods: This randomized double-blind placebo-controlled trial compared 2 g of IV magnesium v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(64 citation statements)
references
References 27 publications
(33 reference statements)
1
63
0
Order By: Relevance
“…The addition of caffeine to paracetamol, aspirin (Migliardi et al, 1994 Level I) or ibuprofen (Diamond et al, 2000 Level II) significantly improved analgesia and a paracetamol-aspirin-caffeine combination was more effective than placebo and all three component drugs alone, in terms of analgesia outcomes and time to effect (Diener et al, 2005 Level II). IV magnesium was ineffective in treating acute TTH in the emergency department (Frank et al, 2004 Level II).…”
Section: Episodic Tension-type Headachementioning
confidence: 99%
“…The addition of caffeine to paracetamol, aspirin (Migliardi et al, 1994 Level I) or ibuprofen (Diamond et al, 2000 Level II) significantly improved analgesia and a paracetamol-aspirin-caffeine combination was more effective than placebo and all three component drugs alone, in terms of analgesia outcomes and time to effect (Diener et al, 2005 Level II). IV magnesium was ineffective in treating acute TTH in the emergency department (Frank et al, 2004 Level II).…”
Section: Episodic Tension-type Headachementioning
confidence: 99%
“…Two small controlled but non-randomised studies have suggested that intravenous magnesium sulphate reduces headache in patients with acute migraine attacks13 and in patients with headache of any type, including migraine, cluster headache and chronic daily hedache 14. However, randomised controlled trials did not show any beneficial effect of intravenous magnesium on migraine15 16 or acute benign headache 17. In most of these studies, magnesium was administered as an intravenous bolus of 1–2 g 15–18.…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium deficiency has been presumed to contribute to the pathogenesis of primary headaches, particularly migraine (Frank, Olson, Shuler, & Gharib, 2004). Research has shown that patients who experience migraine have lower serum magnesium levels during headache exacerbation and during periods without headache (Frank et al, 2004).…”
Section: Magnesiummentioning
confidence: 99%
“…Research has shown that patients who experience migraine have lower serum magnesium levels during headache exacerbation and during periods without headache (Frank et al, 2004). Resultantly, a treatment strategy for patients with headache has been the administration of magnesium (Frank et al, 2004). Frank et al (2004) evaluated the effectiveness of intravenous magnesium for pain relief among patients with primary headache presenting to the ED.…”
Section: Magnesiummentioning
confidence: 99%
See 1 more Smart Citation